Genetically Predicted Circulating Omega-3 Fatty Acids Levels Are Causally Associated With Increased Risk for Systemic Lupus Erythematosus - Wang, Peng; Xiang, Kun; Xu, Yuan-Yuan; He, Yi-Sheng; Hu, Yu-Qian; Ni, Jing; Pan, Hai-Feng (Frontiers in Nutrition, 2022)
Background: Accumulating evidence has demonstrated the associations of omega-3 or omega-6 polyunsaturated fatty acids (PUFAs) with the disease activity and inflammatory mediators of systemic lupus erythematosus (SLE), but the evidence of causal links of omega-3 or omega-6 PUFAs on the risk for SLE remains inconclusive. Objectives: This study was conducted to evaluate the causal relationships between omega-3/omega-6 PUFAs and SLE by performing Mendelian randomization (MR) analysis. Methods: Genome-wide significant single-nucleotide polymorphisms (SNPs) were obtained from genome-wide association studies (GWAS) of circulating omega-3/omega-6 levels (n = up to 13, 544) and GWAS meta-analyses of SLE (n = 14, 267), respectively. The bidirectional two-sample MR (TSMR) analysis was conducted to infer the causality. Results: The inverse-variance weighted (IVW) method revealed that genetically determined per standard deviation (SD) increase in omega-3 levels were causally associated with an elevated risk for SLE (odds ratios [OR] = 1.49, 95% CI: 1.07, 2.08, P = 0.021), but no causal effect of omega-6 on the risk SLE was observed (IVW OR = 1.06, 95% CI: 0.72, 1.57, P = 0.759). In addition, there were no significantly causal associations in genetic predisposition to SLE with the changes of omega-3 and omega-6 levels, respectively (IVW beta for omega-3: 0.007, 95% CI: -0.006, 0.022, P = 0.299; IVW beta for omega-6: -0.008, 95% CI: -0.023, 0.006, P = 0.255). Conclusion: The present study revealed the possible causal role of omega-3 on increasing the risk for SLE, it could be potential implications for dietary recommendations.